The Threat and Cascade Method of estuarine health assessment: a logical sequence from human impact to biological degradation via system physics and chemistry - Stevens, Victoria (Department of Oceanography, 2023)
A methodology for the comparative assessment of estuarine health over a range of systems is presented. It is based on the assumption that anthropogenic impact is the causative variable when considering negative impacts on estuarine health. The methodology follows a logical cascade of estuarine health assessment protocols. The first step in the Threat and Cascade Method (TaCM) incorporates socio-economic to produce a scaled indicator used to identify estuarine systems that are potentially threatened by anthropogenic inputs. The socio-economic algorithm incorporates the following variables: land cover, population density, per capita wealth, state of the estuarine mouth, abstracted mean annual runoff, encroachment of development, estuary use, and sewerage input. If the Socio-Economic Threat Index identifies the estuary as being threatened, then the second stage of the TaCM is initiated. This is an assessment of the system's physics and is accomplished by considering the following variables: residence time, estuary number (freshwater inflow/ tidal prism), coastal exchange, and the proportion of the time the estuary mouth is closed to the ocean. The Threat and Cascade Method assumes that an anthropogenically threatened system with a short residence time is less likely to be impacted on than a threatened system with a long residence time. If the Physical Threat Index identifies the estuary as being threatened, then the third stage of the TaCM is initiated. This involves assessing the chemistry and then the biology of the threatened estuarine system. The TaCM was tested using both local (South African) and international case studies. The results showed that the TaCM has the potential to become a universal methodology. The results also showed that the TaCM allows estuarine researchers and managers to rapidly assess the 'health' of a number of systems, as it mainly concentrates on estuaries that are likely to be impacted upon. The TaCM assessment identifies 'what' is causing the estuary's health to deteriorate, therefore identifying the problem areas that need to be addressed in order to mitigate the impacts on the estuary. This will allow managers to assess the success of remedial action on the estuary. The results also revealed that the TaCM could be used to predict what impact 'change' in the estuary catchment would have on an estuary's health.